2023
DOI: 10.1021/acssuschemeng.3c04373
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Dependent Techno-Economic Analysis of CO2 Capture and Electroreduction to Ethylene

Théo Alerte,
Adriana Gaona,
Jonathan P. Edwards
et al.

Abstract: The decarbonization of the chemical industry is essential to mitigate carbon dioxide (CO2) emissions. Ethylene (C2H4) is the highest production petrochemical globally. When powered by renewable electricity, the electrochemical conversion of CO2 to C2H4 offers a promising route to low carbon C2H4 production. We perform a detailed techno-economic assessment (TEA) of the CO2 reduction reaction (CO2RR) process, converting CO2 from an industrial point source to polymer-grade C2H4. We pair the CO2 electrolyzer with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Nevertheless, the ethanol in the cathodic liquid product stream could be further separated and dehydrated to form C 2 H 4 , which could then be fed into the oligomerization process to enhance the yield of C 8 –C 16 hydrocarbons produced by this route. Ethanol can be separated with an approximately 95 wt % purity via double- or triple-column extractive distillation from the azeotropic mixture of H 2 O, CH 3 COOH, and CH 2 O 2 . , This is followed by ethanol dehydration to produce C 2 H 4 . Ethanol dehydration is a mildly endothermic reaction (Δ H 0 = 45.6 kJ/mol) that can be catalyzed by acid-based catalysts such as silica and alumina .…”
Section: Methods and Process Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the ethanol in the cathodic liquid product stream could be further separated and dehydrated to form C 2 H 4 , which could then be fed into the oligomerization process to enhance the yield of C 8 –C 16 hydrocarbons produced by this route. Ethanol can be separated with an approximately 95 wt % purity via double- or triple-column extractive distillation from the azeotropic mixture of H 2 O, CH 3 COOH, and CH 2 O 2 . , This is followed by ethanol dehydration to produce C 2 H 4 . Ethanol dehydration is a mildly endothermic reaction (Δ H 0 = 45.6 kJ/mol) that can be catalyzed by acid-based catalysts such as silica and alumina .…”
Section: Methods and Process Descriptionmentioning
confidence: 99%
“…This technology is still in an early stage of development, with low TRL. However, it has been reported that enhancing certain short-term technical and economic factors could make direct CO 2 electrolysis a more profitable method for C 2 H 4 production . Therefore, the pathway through the C 2 H 4 intermediate produced by direct CO 2 electrolysis is also compelling and, thus, selected for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Such reactions can facilitate more sustainable routes for chemical transformations, potentially reducing the carbon footprint associated with processes related to climate change mitigation efforts. [4][5][6][7] Identifying rate-limiting steps for processes involving CPET steps remains a key challenge to elucidating the complexities of proton transfer processes and improving existing chemical transformation technologies. 3,[8][9][10][11] Recent advancements in electrocatalysis theory and developments in methods for density functional theory (DFT) have revolutionized our understanding of CPET reactions at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled Proton–Electron Transfer (CPET) reactions are a fundamental process where a proton and an electron are transferred simultaneously in a single kinetic step. Such reactions can facilitate more sustainable routes for chemical transformations, potentially reducing the carbon footprint associated with processes critical to climate change mitigation efforts. Identifying and reducing rate-limiting steps for processes involving CPET steps remains a key challenge toward improving existing chemical transformation technologies. , Recent advancements in electrocatalysis theory and developments in methods for density functional theory (DFT) have revolutionized our understanding of CPET reactions at the atomic level. , These developments have not only provided fundamental insights into reaction dynamics but also improved our ability to predict trends in their rates more accurately, a crucial step toward optimizing the use of such processes in energy conversion and storage.…”
Section: Introductionmentioning
confidence: 99%